Late-onset Lennox-Gastaut syndrome as a phenotype of 15q11.1q13.3 duplication - Rocha, J (2013)
The clinical symptoms associated with chromosome 15q duplication syndrome manifest through a heterogeneous group of symptoms characterised by hypotonia, delay in motor skills and language development, cognitive and learning disabilities, autism spectrum disorder and refractory epilepsy. The late development of Lennox-Gastaut syndrome in patients with 15q11q13 duplication is a possibility that physicians should be aware of. We report the case of a 27-year-old man with a neurodevelopmental syndrome due to a 15q duplication, with intellectual disability, psychiatric disturbances, and an epileptic phenotype diagnosed as late-onset Lennox-Gastaut syndrome.